Body Caudal Undulation Measured by Soft Sensors and Emulated by Soft Artificial Muscles. (20th August 2021) - Schwab, Fabian; Lunsford, Elias T; Hong, Taehwa; Wiesemüller, Fabian; Kovac, Mirko; Park, Yong-Lae; Akanyeti, Otar; Liao, James C; Jusufi, Ardian
Abstract: We propose the use of bio-inspired robotics equipped with soft sensor technologies to gain a better understanding of the mechanics and control of animal movement. Soft robotic systems can be used to generate new hypotheses and uncover fundamental principles underlying animal locomotion and sensory capabilities, which could subsequently be validated using living organisms. Physical models increasingly include lateral body movements, notably back and tail bending, which are necessary for horizontal plane undulation in model systems ranging from fish to amphibians and reptiles. We present a comparative study of the use of physical modeling in conjunction with soft robotics and integrated soft and hyperelastic sensors to monitor local pressures, enabling local feedback control, and discuss issues related to understanding the mechanics and control of undulatory locomotion. A parallel approach combining live animal data with biorobotic physical modeling promises to be beneficial for gaining a better understanding of systems in motion.